The Response to Share Mispricing by Issuing Firms and Short Sellers. (7th May 2023) - Schultz, Paul
Abstract: Short sale constrained stocks are overpriced on average. I show that firms exploit mispricing by selling shares when their stock is short sale constrained and repurchasing shares when their stock is easily shorted. Stocks underperform following seasoned equity offerings (SEOs) if and only if the stock is difficult to short. This suggests that some SEOs are motivated by mispricing, whereas others are not. Short selling costs make it difficult for investors to profit from the poor performance following SEOs. Short selling and SEOs are alternative ways to supply shares to investors, and firms become the low-cost share provider when short selling is costly.